The runaway dolls [compact disc, unabridged] - Martin, Ann M., 1955- (Martin, Ann M., 1955- Doll people story., 2008)
In the final installment of the Doll People trilogy, Annabelle Doll and Tiffany Funcraft face an unexpected visitor, a doll named Tilly May. With her familiar-looking face, Annabelle and Tiffany find themselves wondering if Tilly May could be Annabelle's long-lost sister.